What about if buildings respond to my mood? - Almeida, L.; Eloy, S.; Almeida, A. de. (Formal Methods in Architecture. Advances in Science, Technology & Innovation, 2021)
This work analyzes the possibilities of interaction between the built environment and its users, focused on the responsiveness of the first to the emotions of the latter. Transforming the built environment according to the mood, feelings, and emotions of users, moment by moment, is discussed and analyzed. The main goal of this research is to define a responsive model by which the built environment can respond in a personalized way to the users’ emotions. For such, computational technical issues, building construction elements and users’ interaction are identified and analyzed. Case studies where occurs an interaction between the physical space and users are presented. We define a model for an architecture that is responsive to the user’s emotions assuming the individual at one end and the space at the other. The interaction between both ends takes place according to intermediate steps: the collection of data, the recognition of emotion, and the execution of the action that responds to the detected emotion. As this work focuses on an innovative and disruptive aspect of the built environment, the recognition of the new difficulties and related ethical issues are discussed.